Analysis of the Dynamics of the Brazilian Forward Market of Electricity - Luz, Cristina Pimenta de Mello Spineti; Gomes, Leonardo Lima; Brandão, Luiz Eduardo Teixeira (Review of Business Management, 2012)
Between 1996 and 2003, several countries, including Brazil, began to restructure their electricity sectors and established free markets for energy trading. The growth of these markets has required the adaptation of financial instruments for risk management and return to the particulars of each market. In Brazil, the market still has a disorganized and decentralized over-the-counter market (OTC) structure, which is more difficult to analyze due to the lack of public information. In this setting, the bilaterally negotiated forward contracts for electricity are the primary instruments to mitigate risks and evaluate investments. In this context, the objective of this study is to better understand the dynamics of the forward price of electricity negotiated in Brazil. In this article, we propose a method to construct the forward curve based only on market information and show an application of this approach. Our results indicate that the Brazilian forward market of electricity has a contango behaviour in certain periods, high risk premiums and only partial adherence of forward prices to the expectations of future spot prices. Studies support these evidences. Key words: Electricity trading. Foward market. Risk premium.